Rise time reduction of thermal actuators operated in air and water through optimized pre-shaped open-loop driving. (24th February 2017) - Larsen, T; Doll, J C; Loizeau, F; Hosseini, N; Peng, A W; Fantner, G E; Ricci, A J; Pruitt, B L
Abstract: Electrothermal actuators have many advantages compared to other actuators used in micro-electro-mechanical systems (MEMS). They are simple to design, easy to fabricate and provide large displacements at low voltages. Low voltages enable less stringent passivation requirements for operation in liquid. Despite these advantages, thermal actuation is typically limited to a few kHz bandwidth when using step inputs due to its intrinsic thermal time constant. However, the use of pre-shaped input signals offers a route for reducing the rise time of these actuators by orders of magnitude. We started with an electrothermally actuated cantilever having an initial 10–90% rise time of 85 μ s in air and 234 μ s in water for a standard open-loop step input. We experimentally characterized the linearity and frequency response of the cantilever when operated in air and water, allowing us to obtain transfer functions for the two cases. We used these transfer functions, along with functions describing desired reduced rise-time system responses, to numerically simulate the required input signals. Using these pre-shaped input signals, we improved the open-loop 10–90% rise time from 85 μ s to 3 μ s in air and from 234 μ s to 5 μ s in water, an improvement by a factor of 28 and 47, respectively. Using this simple control strategy for MEMS electrothermal actuators makes them an attractive alternative to other high speed micromechanical actuators such as piezoelectric stacks or electrostatic comb structures which are more complex to design, fabricate, or operate.